The Application Of Instructional Media In Teaching English To Young Learners - Diannita, Artika (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2022)
English is a foreign language, hence not easy to teach English to young learner in Indonesia, thus, need something interesting to teach English to young learners, one of which uses instructional media. Instructional media as a tool needed to facilitate the teachers in presenting the material, but many English teachers in Indonesia find it difficult to use instructional media in the classroom. This study aims to (1) how the teacher applied the instructional media in the classroom. (2) to investigate problems faced by the teacher, and (3) elaborate the teacher's strategies in solving problems using the instructional media. This study was conducted a case study design, by using observation and interviews to collect data. In the investigation teachers do not have free access to use the media provided at school. Thus, they faced obstacles to provide proper media in classroom. Therefore this paper described certain strategies to solve teacher problems in using instructional media in the class. Keywords: Teaching English, Instructional media, Young learners